2018
DOI: 10.1186/s13104-018-3888-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasitic infection among children under 5 years of age at Dessie Referral Hospital: cross sectional study

Abstract: ObjectiveIntestinal parasitic infection is a serious public health problem throughout the world particularly in developing countries. Like other countries in sub saran region epidemiological data regarding prevalence of intestinal parasites and their associated factors were limited in Ethiopia. So, the main objective of this study was to determine the prevalence of intestinal parasites and associated factors among under five children in Dessie Referral Hospital from August 1, 2017 to December 20, 2017.ResultsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
32
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 15 publications
12
32
5
Order By: Relevance
“…The finding of this study was higher than a studies, that were reported from researches done at Dessie referral hospitals was 15.5% among children below 5 years old [27], at Debre-Berhan, Ethiopia among children below 5 years old was 17.3% [28], at University of Gondar Hospital, Gondar, Northwest Ethiopia was 48 (17.3%) among children below 5 years old [29], and at Wonji Shoa, Sugar Estate was 24% [30].…”
Section: Discussioncontrasting
confidence: 72%
“…The finding of this study was higher than a studies, that were reported from researches done at Dessie referral hospitals was 15.5% among children below 5 years old [27], at Debre-Berhan, Ethiopia among children below 5 years old was 17.3% [28], at University of Gondar Hospital, Gondar, Northwest Ethiopia was 48 (17.3%) among children below 5 years old [29], and at Wonji Shoa, Sugar Estate was 24% [30].…”
Section: Discussioncontrasting
confidence: 72%
“…histolytica, G. lambilia and C. parvum were the most prevalent protozoan parasites in our study cohort. The high prevalence of E. histolytica/dispar (36.1%) in our study is in agreement with previous reports (54,58,72). Consequences of childhood E. histolytica infection include malnourishment, anaemia and stunted growth (25).…”
Section: Factors Associated With Anaemia Among Pre-school Age Childrensupporting
confidence: 93%
“…The association between ngernail hygiene and intestinal parasitic infection was determined from seven studies with a sample size of 5,155 (16,21,23,29,37,50,51). The result of this analysis shows signi cant association between ngernail hygiene and IPI.…”
Section: Factors Associated With Intestinal Parasite Infectionmentioning
confidence: 99%